Comparison between clinical examination and magnetic resonance imaging in accurately diagnosing meniscal tears - Mamillapalli, Siva K.; Chowdam, Jagan B. (International Journal of Research in Orthopaedics, 2022)
Background: The primary goal of this study was to examine the correlation between clinical results, MRI scans, and Arthroscopic findings in the case of meniscal injury. We compared various parameters between clinical findings and MRI findings in case of suspected meniscus injury cases keeping Arthroscopy findings as the gold standard. Methods: Patients coming to our OPD with complaints of knee pain were examined by an experienced orthopaedic surgeon. The sample size of our study was 60 cases. All suspected meniscal tear cases underwent clinical examination, MRI scanning and Arthroscopic examination to assess the relationship between clinical findings and MRI findings, keeping Arthroscopy findings as a gold standard. Results: For the diagnosis of medial and lateral meniscus tears, a clinical evaluation carried out by an experienced orthopaedic surgeon exhibited greater sensitivity, specificity, precision, and negative and positive predictive values than MRI. Conclusions: A clinical evaluation by an experienced orthopaedic surgeon yielded superior outcomes than an MRI for diagnosing meniscal injuries. MRI is indicated in case of complex knee injuries.